Pengaruh Locus Of Control Terhadap Kepuasan Kerja Pada Grapari Telkomsel Kota Bima - Zulfikar; Wulandari; Amirul Mukminin (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of Locus Of Control on Job Satisfaction at Grapari Telkomsel, Bima City. Where there are still many assignments that are outside of the field or expertise, so the employee needs time to adjust or learn more about the assigned task. This research is included in the category of associative research using a quantitative approach. The number of samples is 34 employees who work at Grapari Telkomsel, Bima City. Based on the results of the partial test (t test) shows that there is a positive and significant effect on the LOC variable on job satisfaction of Grapari Telkomsel Telkomsel employees in Bima City. Further development of further research variables can be developed by including compensation and performance allowance variables in order to assess employee performance satisfaction